Extending axial focus of optical coherence tomography using parallel multiple aperture synthesis - Bo, En (2019)
Compromising the inherent trade-off between transverse resolution and depth of focus (DOF) remains a long-standing issue in optical coherence tomography (OCT). In this work, we report a novel technique—parallel multiple aperture synthesis (pMAS) to simultaneously generate multiple optical apertures in an OCT sample arm by employing a two-surface coated mirror. In the proposed pMAS, the DOF is extended by a factor of 16.49 without sacrificing the transverse resolution for proof-of-concept experiments when multiple distinctive apertures are digitally synthesized. The microparticles and tissue experiments demonstrate the feasibility of pMAS to address the fundamental problem of limited DOF in high-resolution OCT.